Recurrent Somatic MAP2K1 Mutations in Papillary Thyroid Cancer and Colorectal Cancer - Bu, Rong; Siraj, Abdul K.; Masoodi, Tariq; Parvathareddy, Sandeep Kumar; Iqbal, Kaleem; Al-Rasheed, Maha; Haqawi, Wael; Diaz, Mark; Victoria, Ingrid G.; Aldughaither, Saud M.; Al-Sobhi, Saif S.; Al-Dayel, Fouad; et al. (Frontiers in Oncology, 2021)
Mitogen-activated protein kinase kinase 1 (MAP2K1) is a dual specificity protein kinase that phosphorylates both threonine and tyrosine residues in ERK. MAP2K1 mutations have been identified in several cancers. However, their role in Middle Eastern papillary thyroid cancer (PTC) and colorectal cancer (CRC) is lacking. In this study, we evaluated the prevalence of MAP2K1 mutations in a large cohort of Middle Eastern PTC and CRC using whole-exome and Sanger sequencing technology. In the discovery cohort of 100 PTC and 100 CRC cases (comprising 50 MAPK mutant and 50 MAPK wildtype cases each), we found one MAP2K1 mutation each in PTC and CRC, both of which were MAPK wildtype. We further analyzed 286 PTC and 289 CRC MAPK wildtype cases and found three MAP2K1 mutant PTC cases and two MAP2K1 mutant CRC cases. Thus, the overall prevalence of MAP2K1 mutation in MAPK wildtype cases was 1.1% (4/336) in PTC and 0.9% (3/339) in CRC. Histopathologically, three of the four MAP2K1 mutant PTC cases were follicular variant and all four tumors were unifocal with absence of extra-thyroidal extension. All the three CRC cases harboring MAP2K1 mutation were of older age (> 50 years) and had moderately differentiated stage II/III tumors located in the left colon. In conclusion, this is the first comprehensive report of MAP2K1 somatic mutations prevalence in PTC and CRC from this ethnicity. The mutually exclusive nature of MAP2K1 and MAPK mutations suggests that each of these mutation may function as an initiating mutation driving tumorigenesis through MAPK signaling pathway.